Post-Divorce Parenting: Characteristics Related to the Assignment of Custody of Children after the Breakdown of Heterosexual Marriages - Jiménez-Cabello, José Manuel; Puertas-Cañavera, Inmaculada; Paniza-Prados, José Luis; García-Moreno, José Manuel (Revista de Estudios Andaluces, 2021)
This research focuses on the analysis of the variables of a social nature that affect the assignment of custody after divorce from heterosexual marriages in Andalusia. For this, a quantitative methodology is used, using the Statistics of Nullities, Separations and Divorces (INE, 2017) and data from economic indicators such as Gross Domestic Product (2017). Its exploitation allows taking into account a whole set of variables necessary to understand the phenomenon under study. Descriptive and multivariate analyzes are carried out (factorial and correspondence analysis). The main results obtained confirm that variables such as the number of dependent minor children or dependent children of legal age, the judgment failure and the GDP of each province are significantly related to the custody modality finally assigned. Other variables such as the age of the spouses or their nationality do not seem to have an association in the modality that is granted.